Preparation, characterization, and electrochemical properties of KOH-activated carbon from cassava root - Suphawi Chaisit; Narong Chanlek; Jessada Khajonrit; Thongsuk Sichumsaeng; Santi Maensiri (Materials Research Express, 2020)
This work reports the electrochemical properties of activated carbon prepared from cassava starch activated using KOH. The effect of the impregnation ratios by weight on the surface area and pore structure of the prepared carbon was characterized by N _2 adsorption-desorption techniques. By increasing the impregnation ratio by weight from 1:1 to 1:5, the specific surface area increased from 1049 to 1350 m ^2 g ^−1 and mean pore diameter also increased from 1.89 to 2.15 nm, respectively. The decrease of mean pore diameter enhanced the specific capacitance value. The carbon electrode with the impregnation ratio of 1:1 reached the maximum specific capacitance of 175 ± 12 F g ^−1 at the current density of 2 A g ^−1 due to the smaller mean pore size. Moreover, the specific capacitance retained about 98% after 1000 cycles. The excellent electrochemical performance of activated carbon prepared from cassava starch could be considered as an electroactive material for supercapacitors.